2022
DOI: 10.3390/ijerph19041915
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Victimization, Self-Efficacy to Refuse Sex While Drinking, and Regretting Alcohol-Involved Sex among Underserved Youth in Kampala, Uganda

Abstract: The purposes of this study were to determine whether youth who have experienced sexual victimization (SV) have lower self-efficacy to refuse sex and to identify intervention strategies for rape survivors to mitigate further health-risks and harm. Cross-sectional data from the 2014 Kampala Youth Survey (n = 1134) of youth aged 12 to 18 years recruited from Uganda Youth Development Link drop-in centers were used to conduct the analyses. Multivariable statistics were computed to determine the correlates (i.e., se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…That is, if agency declines, then people are less likely to be empowered to make informed decisions regarding SRH decisions [2]. Some of the literature has suggested that early sexual debut is largely a result of poor self-efficacy to negotiate refusal sex [21], which can be in the form of delayed sex [22] or sexual abstinence [23,24]. Low self-efficacy may lead to low or non-condom use [25][26][27][28] or non-use of contraception [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…That is, if agency declines, then people are less likely to be empowered to make informed decisions regarding SRH decisions [2]. Some of the literature has suggested that early sexual debut is largely a result of poor self-efficacy to negotiate refusal sex [21], which can be in the form of delayed sex [22] or sexual abstinence [23,24]. Low self-efficacy may lead to low or non-condom use [25][26][27][28] or non-use of contraception [29,30].…”
Section: Introductionmentioning
confidence: 99%